Evaluasi Kebutuhan Dan Kinerja Pelayanan Parkir Dan Sistem Antrian Pada Pusat Perbelanjaan Di Bandar Lampung (Studi Kasus: Areal Parkir Transmart Carrefour Bandar Lampung) - Nugraha, Arya; Putra, Sasana; Herianto, Dwi (Universitas Lampung, 2019)
The purpose of this research is to analyze the performance of the queuing system and parking needs at Bandar Lampung Mall Transmart Carefour. With various kinds of facilities available at Transmart Carrefour Mall, it can affect the number of visitors or the number of customers who come. The survey was conducted for 1 day and the observations were carried out for 10 hours at 10:00 to 20:00 WIB.This research was conducted in the parking area of the Transmart Carefour Mall and this survey included recording the number of vehicles, recording the number of vehicle police and the service time of vehicles entering and leaving the study site. The results of research on parking needs obtained the highest accumulation occurred on Saturday at 15.01-15.30 WIB namely 162 vehicles. The unit of car parking space (SRP) currently is 300 slots. With the accumulation and number of parking spaces, the available parking lots are not enough in the standard value but what happens in the field, the SRP can still accommodate customers who come. The highest average arrival rate at the entrance is 16 vehicles/hour with a service time of 15.6 seconds/vehicle. Thus there is still a lot of freedom in the parking gate, with the gate idle probability value of 0.366, so the parking gate is not too busy. Keywords: Parking Accumulation, Parking Space Unit, Arrival Rate, Service Time